2007
DOI: 10.1007/bf02913334
|View full text |Cite
|
Sign up to set email alerts
|

An extended chemical analysis of gallstone

Abstract: Chemical composition of gall stones is essential for aetiopathogensis of gallstone disease. We have reported quantitative chemical analysis of total cholesterol bilirubin, calcium, iron and inorganic phosphate in 120 gallstones from haryana. To extend this chemical analysis of gall stones by studying more cases and by analyzing more chemical constituents. A quantitative chemical analysis of total cholesterol, total bilirubin, fatty acids, triglycerides, phospholipids, bile acids, soluble proteins, sodium potas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
45
3
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 18 publications
25
45
3
1
Order By: Relevance
“…Estrogens increase cholesterol secretion and diminish bile salt secretion, while progestins act by reducing bile salt secretion and impairing gallbladder emptying leading to stasis. 13 In this study, as per gross morphology, majority of cases (44) had pigmented stones. On the other hand, as per biochemical analysis, majority of cases (33) had mixed type of stones.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Estrogens increase cholesterol secretion and diminish bile salt secretion, while progestins act by reducing bile salt secretion and impairing gallbladder emptying leading to stasis. 13 In this study, as per gross morphology, majority of cases (44) had pigmented stones. On the other hand, as per biochemical analysis, majority of cases (33) had mixed type of stones.…”
Section: Discussionmentioning
confidence: 56%
“…While a study done in Haryana by Chandran et al showed 26%, 38% and 36%, respectively. 13 Mixed and pigment stones are common in northern India. 2 We observed that most (43, 71.7%) patients presented with the complaints of pain in the region of hypochondrial region followed by nausea in 46.6%.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were agreed with pervious report that mentioned the major of chemical constituent stones is calcium compounds. Chemical composition of gallstones is essential for aetiopathogensis of gallstone disease (Chandran et al, 2007). Mixed stones composed from including calcium, uric acid, magnesium, phosphate and oxalate, this result constant with pervious finding that also mentioned the pure uric acid stones are relatively rare (Morton et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…A quantitative chemical analysis of total cholesterol, total bilirubin, fatty acids, triglycerides, phospholipids, bile acids, soluble proteins, calcium, sodium potassium, magnesium, copper, oxalate and chlorides as minor components were found in all types of calculi (Chandran et al, 2007). Studies on gallstone composition carried out in different parts of the world indicate a close link…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation